P-201 Cardiac Manifestations of Pediatric Inflammatory Bowel Disease. (March 2016) - Bass, Julie; Shakhnovich, Valentina; Carpenter, Ellen; Radford, Kim; McCullough, Jennifer
Abstract : Background: Although inflammatory cardiac diseases share common inflammatory cytokines (i.e. IL-6, IL-8, TNF-α) with Inflammatory Bowel Disease, cardiac extra-intestinal manifestations in IBD are uncommon and typically attributed to drug hypersensitivity reaction to medications used to treat IBD, especially mesalamine. We present 3 cases of rare cardiac manifestations of pediatric IBD that occurred within 6 months. Methods: Case 1: A previously healthy10 year old boy presented with presumed recurrent viral gastroenteritis, 10 pound weight loss, abdominal pain, vomiting, and inconsistent stooling pattern. Plain film of the abdomen revealed significant cardiomegaly. A large pericardial effusion of unknown etiology was noted and drained. Repeat drainage of the effusion was required the following month. He was treated with non-steroidal anti-inflammatory medication and subsequently hospitalized with abdominal pain and significant elevation of inflammatory markers. Family history revealed Ulcerative Colitis. Endoscopy showed mild erythema of the rectum and cecum with evidence of chronic inflammation on histopathology suggestive of IBD. MRE was unremarkable. The patient was treated with infliximab and had nearly complete resolution of the effusion after 3 doses. Case 2: A 17-year-old male with history of chronic constipation and recurrent urinary tract infections presented with acute chest pain. Evaluation revealed significant troponin elevation, EKG ST segment elevation with reciprocal depressions and minimal pericardial effusion on echocardiogram. Cardiac catheterization was unremarkable. Cardiac MRI was consistent with myocarditis and subsequent echocardiogram showed complete resolution of the effusion with normal ejection fraction. Two months later, patient returned with 10 pound weight loss, elevated inflammatory markers, and anemia. Endoscopy showed focal active duodenitis and ileitis. MRE showed marked inflammatory changes of terminal ileum and sigmoid colon with amorphous collection within the central pelvis. CT showed distal ileitis with enterocolonic fistula to the sigmoid colon and probable enterovesical fistula to the posterosuperior bladder wall, consistent with Crohn's disease (CD). Treatment with steroids, antibiotics, and infliximab therapy induced good clinical response. Results: Case 3: A 13-year-old boy presented for evaluation of diarrhea, 30 pound weight loss and elevated inflammatory markers. Endoscopy and histopathology was consistent with Crohn's disease with active chronic gastritis and duodenitis, mild architectural distortion in terminal ileum, and mild acute and chronic inflammation throughout the colon. Capsule endoscopy revealed multiple areas of small bowel ulceration. Initial treatment included steroids and azathioprine with good therapeutic response. Six months later, however, he developed symptom recurrence and elevated inflammatory markers. MRE revealed active small bowel disease with incidental findings of small pericardial and bilateral pleural effusions. He was asymptomatic from a cardio-respiratory standpoint. Therapy was advanced to infliximab, which induced good clinical response. Effusions were resolved after 2 doses. Conclusions: These 3 cases of cardiac manifestations in newly diagnosed pediatric IBD patients highlight a rare extra-intestinal manifestation that is unlikely a result of drug hypersensitivity as 2 of the 3 cases were treatment naive at the time of cardiac findings. All 3 patients were ultimately treated with anti-TNF therapy and responded well, perhaps due to a common inflammatory cytokine driving the intestinal and extra-intestinal disease.